Perceptions of the secondary students towards the use of english at eca, a North American school in Bogotá (2017)
This qualitative research studies the secondary students` perceptions towards the use of English at ECA, a multicultural North American Christian school located in Bogotá, Colombia. The researchers attempt to explore the students` perspectives related to the use of English in their context. A total of seventeen students, both female and male, were selected from 8th to 11th grades, with ages ranging from 13 to 18 years old. A survey and an interview were elaborated by the researchers, and students actively participated in the development of these instruments. There were also some observations inside and outside the classrooms where the investigators had the opportunity to take notes of the target population. Considering the narrative description research method and the data analysis triangulation methodology, the data collected was transcribed, classified and analyzed in three different categories which are: The privilege of being part of an English speaking school (ECA), The English policy during school hours, and Usefulness and proficiency of the use of English. These categories aimed to characterize the students`perceptions in a feasible way. The results showed relevant information about their unique context where they daily interact academically and socially using English as a bridge of communication with foreign teachers and students. The study shows that students recognize and have a sense of belonging within the school context. They are happy to have native North American teachers who teach all subjects in the English language and this lets them have real immersion. Besides, students highlight the importance of being bilingual. They identify English as a tool that offers good career and job opportunities, not only in Colombia but around the world. Some students are confident using English, while others are not. Spanish is also as important as English is for Colombians and foreigners in order to communicate among them. The study also reflects on students´ different opinions about the English expectation rule. Some students agree saying that the rule is to be complied with and it is relevant, and other participants are in disagreement and would like the norm to have exceptions since there are hard moments to use English during school day.